Effect of disclosure Sustainability Report on company value with company performance as intervening variables in the company Go Public listed on Indonesia stock exchange - Lyan, Marcella Reobita; Defung, Felisitas; Fakhroni, Zaki (Technium Social Sciences Journal, 2021)
Significant changes occur as at this time, companies are required to increase their knowledge, make new updates to keep up with the times. Learning procedures are at the root of the company’s strength to adapt to the significant changes occurring in the business world. This is done in particular with a sustainable development plan for the entire company. In this study, IDX companies use the manufacturing and mining sectors. The research sample is 21 companies with a period of 5 years so the total sample is 105 data. Variables consist of exogenous, endogenous and intervening. This study applies the PLS-SEM analysis tool with measurement tools or supporting applications for WarpPLS 5.